Impact of the perceived quality of education in business schools on competitiveness - Pantelic, Darko; Šereš, Laslo; Milovanov, Olja (Industrija, 2014)
National competitiveness becomes increasingly more relevant in the globalized and interconnected world. This paper aims to summarize main ideas around national competitiveness, its antecedents and indicators, followed by primary research of students’ perception of nature of competitive advantage and their personal competitiveness in intertwined global environments. Primary data was collected in four universities in Austria, Croatia, Serbia and USA. Special emphasis is dedicated to pessimism/optimism as extrapolation of personal confidence in the future. The main contribution of the research lies in understanding the place and role of the business education in enhancing competitiveness, whilst for higher education management, the findings provide better understanding of potential avenues for improvements that will result in increased students’ confidence levels, with positive impact loyalty and image of business schools. Furthermore enhancement of satisfaction levels among students with overall quality of business education will not alone contribute to optimism and belief in future, and may not be sufficient for securing nation’s intellectual capital.